DETERMINATION OF ARSENIC INDUCED NUCLEAR ABNORMALITIES IN PERIPHERAL BLOOD ERYTHROCYTES OF CARPS USING MICRONUCLEUS TEST - S. Kousar; M. Javed (Journal of Animal and Plant Sciences, 2016)
Genotoxic effects of arsenic, in-terms micronuclei (MN) frequency and frequency of other nuclear abnormalities (ONA), on four carp species (Labeo rohita, Cirrhina mrigala, Catla catla and Ctenopharyngodon idella) were studied at constant water temperature (30 ºC), pH (7.5) and total hardness (300 mgL-1). Acute toxicity of arsenic in-terms of 96 hr LC50 and lethal concentration for fish was determined and then all fish species were exposed to four sub-lethal (17, 25, 33 and 50% of 96 hr LC50) concentrations of arsenic, separately, for a period of 30 days. As the fish blood erythrocytes are nucleated therefore, selected for determination of genotoxic effects of arsenic. After metal exposure, frequency of (MN) and ONA were observed. All the four fish species showed significantly variable sensitivity to arsenic. Among four fish species, Cirrhina mrigala showed significantly higher micronuclei frequency with the mean value of 37.59 ± 12.49%, followed by that of Labeo rohita, Catla catla and Ctenopharyngodon idella. Mean frequency of other nuclear abnormalities was significantly higher in erythrocytes of Cirrhina mrigala, followed by that of Catla catla, Ctenopharyngodon idella and Labeo rohita with the mean values of 27.68 ± 10.22, 17.52 ± 11.02, 15.54 ± 4.40 and 11.36 ± 5.73%, respectively.
Keywords: Fish; Arsenic; Acute toxicity; Micronuclei; Other nuclear abnormalities; Peripheral blood erythrocytes